2022
DOI: 10.3389/fpsyt.2022.956168
|View full text |Cite
|
Sign up to set email alerts
|

Excessive smartphone use and its correlations with social anxiety and quality of life among medical students in a public university in Malaysia: A cross-sectional study

Abstract: IntroductionSmartphone usage has significantly increased in the last decade among young adults has significantly increased in the last decade. While its benefits are undeniable, its negative implications are increasingly emerging. Studies are needed to investigate the effects of excessive smartphone use on a young person's life. This study aimed to determine the prevalence of excessive smartphone use among medical students and its relations with social anxiety, self-esteem, and quality of life.MethodsA cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Correlations between PA parameters at 6 months after TKA and knee flexion and extension ROM, knee-extension muscle strength, knee pain, and TUG before TKA were analyzed using Pearson’s correlation coefficient when the variables were normally distributed and Spearman’s rank correlation coefficient when the variables were not normally distributed. Variables determined to be significant ( p < 0.05) in the correlation analysis were included as independent variables in a hierarchical multiple linear regression analysis to evaluate factors associated with PA parameters at 6 months after TKA [ 42 , 43 ]. Each model had 2 steps.…”
Section: Methodsmentioning
confidence: 99%
“…Correlations between PA parameters at 6 months after TKA and knee flexion and extension ROM, knee-extension muscle strength, knee pain, and TUG before TKA were analyzed using Pearson’s correlation coefficient when the variables were normally distributed and Spearman’s rank correlation coefficient when the variables were not normally distributed. Variables determined to be significant ( p < 0.05) in the correlation analysis were included as independent variables in a hierarchical multiple linear regression analysis to evaluate factors associated with PA parameters at 6 months after TKA [ 42 , 43 ]. Each model had 2 steps.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated a significant correlation between excessive usage of social media platforms and the presence of depressive symptoms and anxiety disorders. In addition, the aforementioned addictive conduct has been observed to negatively impact the self-esteem and decision-making capacities of students (Sahimi et al, 2022). The phenomenon of social media addiction is a significant concern that necessitates careful consideration and examination.…”
Section: Introductionmentioning
confidence: 99%